Another serious misunderstanding: Jung, Giegerich and a premature requiem. Issue 1 (February 2015) - Saban, Mark
Abstract Barreto's paper, 'Requiem for analytical psychology' utilized Jung's dreams and visions to argue for the obsolescence of Jungian psychology. Its thesis rested upon the theoretical assumptions of Giegerich's psychology as a Discipline of Interiority, which he and Giegerich claim are themselves based in Jung's psychology. Here I argue that that claim is misplaced because it depends upon a fundamental misunderstanding of the nature of Jung's psychological project. I shall further argue that Giegerich's arguments for a Jungian basis to his psychology rely upon misreadings and decontextualisations of Jung's original texts. Finally, I shall attempt to draw attention to the weaknesses and contradictions involved in Barreto's interpretations of Jung's dreams and visions.